2018
DOI: 10.1186/s12902-018-0230-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between ERα/β gene polymorphisms and osteoporosis susceptibility and bone mineral density in postmenopausal women: a systematic review and meta-analysis

Abstract: BackgroundMany studies have reported associations between estrogen receptor (ER) gene polymorphisms and postmenopausal osteoporosis (PMOP) risk and bone mineral density (BMD), but the results are controversial. The aim of the present meta-analysis is to verify the association between ERα and ERβ gene polymorphisms and osteoporosis susceptibility and BMD in postmenopausal women.MethodsPubMed, EMBASE, Web of Science, the Cochrane Library and China WeiPu Library were searched. OR and WMD with 95% CI were calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…A meta-analysis of 30 studies published by Ioannidis et al [ 33 ] showed a positive effect of GG genotype on BMD and fracture risk, whereas rs2234693 polymorphism was not associated with these traits. In a recent review and meta-analysis of Zhu et al [ 34 ] the authors found significant associations of ESR1 polymorphisms with BMD in Caucasian women. The GG and AG genotypes were associated with increased FN BMD and FN Z value, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 30 studies published by Ioannidis et al [ 33 ] showed a positive effect of GG genotype on BMD and fracture risk, whereas rs2234693 polymorphism was not associated with these traits. In a recent review and meta-analysis of Zhu et al [ 34 ] the authors found significant associations of ESR1 polymorphisms with BMD in Caucasian women. The GG and AG genotypes were associated with increased FN BMD and FN Z value, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…After menopause, the reduced ovarian synthesis of estrogen in women results in bone loss, thereby causing osteoporosis [ 29 ]. Additionally, estrogen is a regulator of bone metabolism, and a reduction in estrogen concentration results in BMD loss, increased mechanical loading, induced bone remodeling, and postmenopausal osteoporosis development [ 30 , 31 ]. It has been demonstrated in studies on mice that the functional ESR and Wnt/β-catenin signaling pathways interact in regulating bone mass adaptation in response to mechanical loading [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of OP is largely determined by genetic factors. Numerous studies have demonstrated that genetic variances in the estrogen receptor (ER) gene (21,22), vitamin D receptor (VDR) gene (23,24), and genes of the RANKL-RANK-OPG system (25) are implicated in regulating bone metabolism and influencing bone mass. Additionally, LRP5, a co-receptor of the Wnt pathway, was previously reported as a potential factor in the development of OP (26).…”
Section: Discussionmentioning
confidence: 99%